Intervensi Penggunaan Pembalut Selama Masa Menstruasi pada Wanita Usia Subur Suku Anak Dalam Desa Bukit Suban Sarolangun - Asparian Asparian; Siti Mashirotul Khoiriyah; La Ode Reskiaddin; Hubaybah Hubaybah; Sri Astuti Siregar (Universitas Baiturrahim, 2023)
Women of Reproductive Age of the indigenous people have a hereditary culture or habit of women of childbearing age who have menstruated or tebiek in SAD language to keep them clean unlike the usual women who use sanitary napkins. They only use a long piece of cloth wrapped around their body such as a bra and do not use other clothing or pads during menstruation. The purpose of this study was to analyze the behavior of using sanitary pads during the menstrual period of Women of Reproductive Age of the indigenous people in Bukit Suban Village, Air Hitam District, Sarolangun Regency in 2022.This research is a quantitative study with a quasi-experimental method with a non-equivalent group design. The research population was Women of Reproductive Age of the indigenou people, totaling 96 people in the Tumenggung Grib group. The sample technique is purposive sampling, was taken from 2 groups, namely 16 women in the treatment group and 16 women in comparison according to the inclusion and exclusion criteria. Data collection used a questionnaire and data analysis was carried out using the Paired-Samples T-Test and the Independent Samples T-Test. The results showed that there was a significant increase in the knowledge, attitudes and behavior of the treatment group. Independent Samples T-Test statistical test p value = 0.00 or p value < α in knowledge, attitude and behavior. This indicates that there is a significant difference between the values of the treatment group and the comparison group on the variables of knowledge, attitudes and behavior at indigenous women in Bukit Suban Village, Sarolangun Regency in 2022. Sanitary napkin media as a teaching tool for learning simulations has a major influence in increasing the knowledge, attitudes and behavior of indigenous Women of Reproductive Age as an effort to maintain reproductive health by implementing the practice of using pads in Bukit Suban Village, Sarolangun Regency in 2022